DESKRIPSI KEIKUTSERTAAN PELATIHAN KADER POSYANDU TENTANG DIFTERI DAN PENCEGAHANNYA - Nurfa Tiarana Anggraini; Ari Pristiana Dewi; Wan Nishfa Dewi (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2018)
Diphtheria is an infection caused by the bacterium Corynebacteriumdiphtheria. This study aims to find out the training participation posyandu cadre at Puskesmas Lima Puluh Pekanbaru about diphtheria and its prevention. With a descriptive quantitative research design, 100 respondents as research sample were taken based on the inclusion criteria using cluster sampling technique. Questionnaire was given to participants as measurement tools for demographic data. The analysis used is univariate analysis to determine frequency distribution. The results showed that as many as 66 respondents (66.0%) did not take diphtheria training and 34 respondens (34.0%) attended diphtheria training. It is recommended to health workers to be able to provide more training to cadres about diphtheria and its prevention as the goal of increasing cadre knowledge to be better.Keywords: Cadre, diphtheria, participation, posyandu